2000
DOI: 10.1177/089686080002000109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pyrazinamide and Probenecid on Peritoneal Urate Transport Kinetics during Continuous Ambulatory Peritoneal Dialysis

Abstract: Objective We administered pyrazinamide (PZA) and probenecid (PB) — two well-known modulators of urate transport via the proximal tubules — to evaluate their impact on urate transport through the peritoneal membrane and to clarify mechanisms affecting peritoneal transport. Setting A continuous ambulatory peritoneal dialysis (CAPD) unit in 2nd Hospital of IKA (Social Services Institute), Greece. Patients In 20 stable CAPD patients, on the study day, a 4-hour, 2-L, 1.36% glucose exchange was performed (control ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Results of the present study do not show significant effects of losartan, prazosin, or verapamil on peritoneal transport of glucose, urea, creatinine, sodium, potassium, or total protein during a standard 4-hour PET. These results are in agreement with some previous studies (2,11,19) but contrast with others in which intraperitoneal drugs were used (1,4). No significant changes in D/P creatinine were found with oral enalapril (8), pyrazinamide, or probenecid (11) in the only two other studies reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of the present study do not show significant effects of losartan, prazosin, or verapamil on peritoneal transport of glucose, urea, creatinine, sodium, potassium, or total protein during a standard 4-hour PET. These results are in agreement with some previous studies (2,11,19) but contrast with others in which intraperitoneal drugs were used (1,4). No significant changes in D/P creatinine were found with oral enalapril (8), pyrazinamide, or probenecid (11) in the only two other studies reported in the literature.…”
Section: Discussionsupporting
confidence: 92%
“…In one study, oral enalapril significantly increased the dialysate-to-plasma ratio (D/P) of creatinine (8). In other works, enalapril and nifedipine increased the peritoneal clearance of creatinine and β2-microglobulin (10), and pyrazinamide and probenecid increased the peritoneal transport of urate (11).…”
mentioning
confidence: 91%
“…The exception to the rest of the solutes measured in this study was urate, which exhibited a shorter time constant than predicted for its molecular weight, possibly because it is an ion, although this usually results in longer time constants. This has not been reported previously, although there are data that suggest that unrestricted diffusion is not the only mechanism of urate transport across the peritoneal membrane [13].…”
Section: Total Body Watermentioning
confidence: 66%
“…There might be a slight interaction of urate with albumin, but literature data are ambiguous on this point. The apparently modulating effect on urate transport observed with certain drugs, such as pyrazinamide and probenecid, is intriguing and requires further investigation, especially whether there could be some interactions of these drugs with the association of urate with plasma proteins (albumin) (89).…”
Section: Lactate and Uratementioning
confidence: 99%